Gold as a protective instrument in the phase of national and global economic crisis - Yu. Konopleva; O. Pakova; A. Khakirov (Вестник Северо-Кавказского федерального университета, 2022)
The paper studies gold as a protective asset in the crisis phase by comparing the changes in key indicators of the economy and financial market dynamics with the gold price to identify patterns. Identified the main factors of influence on the change in the gold price from 2008 to the present. On the basis of the main stereotypes about gold two hypotheses have been formed. Disproved the hypothesis of the use of gold as an asset in the investment portfolio for all types of investors to offset the effects of high inflation in times of crisis. The significance of gold in the formation of foreign exchange reserves in the context of growing geopolitical tensions was assessed.